Relationship Between Salted Fish Consumption and Nasopharyngeal Carcinoma: An Evidence-based Case Report - Ikhwanuliman Putera; M. Gema Ramadhan; Shafira Anindya; Natalia R Sutanto; Arief Kurniawan; F. Nikodemus Hosea; Eka D Safitri (Acta Medica Indonesiana)
Aim: to know the relationship between salted fish consumption and nasopharyngeal carcinoma (NPC). Methods: we searched for the articles from PubMed® and ScienceDirect® based on our clinical question. After filtered with our in- and exclusion criteria, we had six articles about this topic, all of them were case-control studies. All articles were then critically appraised for their validity, importance, and applicability. Results: there was no consistent relationship between salted fish consumption and NPC. Worth to note that those studies wo showed the firm relationship were conducted in Southern China, where the incidence of NPC was extremely high and related to specific Chineese-style salted fish consumption. Conclusion: there was an inconsistent relationship between salted fish consumption and NPC.